2007
DOI: 10.1111/j.1464-410x.2007.07044.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of suplatast tosilate (IPD‐1151T) in a rat cystitis model induced by intravesical hydrochloric acid

Abstract: or prednisolone (5 mg/kg) for 7 days, cystometry was performed under urethane anaesthesia. The bladder from HCl-induced cystitis rats was also assessed histopathologically. RESULTSOn cystometrography there was frequent voiding in cystitis rats. Administration of IPD-1151T for 7 days after intravesical HCl instillation dose-dependently increased the micturition volume and intercontraction intervals. Treatment with prednisolone had similar therapeutic effects. Histological analyses in the bladder from cystitis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…In addition, although rats with repetitive administration of cyclophosphamide have frequently been used as another chronic cystitis model (28,61), this animal model requires one-time application of HCl and exhibits histological changes including mastcytosis in the bladder. Although the robust inflammatory changes seen in rats with HCl-induced cystitis are not usually found in the human bladder of PBS/IC, the increased number of mast cells and their degranulation resulting in release of chemical mediators, such as histamine or nerve growth factor, are reportedly linked to neural changes in humans with PBS/IC (26,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although rats with repetitive administration of cyclophosphamide have frequently been used as another chronic cystitis model (28,61), this animal model requires one-time application of HCl and exhibits histological changes including mastcytosis in the bladder. Although the robust inflammatory changes seen in rats with HCl-induced cystitis are not usually found in the human bladder of PBS/IC, the increased number of mast cells and their degranulation resulting in release of chemical mediators, such as histamine or nerve growth factor, are reportedly linked to neural changes in humans with PBS/IC (26,51).…”
Section: Discussionmentioning
confidence: 99%
“…Bladder inflammation was induced according to a previously used method (26). Briefly, a polyethylene catheter (PE-50) was inserted transurethrally into the bladder under pentobarbital (50 mg/kg ip) anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…1a,b). 8 It has also been reported that the HCl‐induced chronic cystitis rats showed bladder hyperalgesia mediated by C‐fiber afferent neurons. 9 Figure 1c shows the data on the eosinophils and mast cell counts in the bladder of the chronic cystitis and sham rats.…”
Section: Basic Experimental Effect Of Ipd‐1151t On Hydrochloric Acmentioning
confidence: 95%
“…A more direct evidence linking chronic inflammation with functional changes in C-fiber afferents has been derived from a rat model of chronic cystitis induced by systemic application of cyclophosphamide, which undergoes hepatic metabolism to acrolein, an irritant excreted in the urine71 or intravesical application of hydrochloric acid (HCI) 72. In the cyclophosphamide model, it has been documented that the majority of bladder afferent neurons from both control and chronic cystitis rats are capsaicin sensitive and exhibit tetrodotoxin-resistant action potentials, whereas those from treated rats exhibit significantly lower thresholds for spike activation and show high-frequency firing characteristics 73.…”
Section: C-fiber Activation In Ic/pbs Pathology and Pain Managementmentioning
confidence: 99%